The Effects of Resilience and Cyberbullying on Self-Esteem. Issue 3 (October 2019) - Aliyev, Ramin; Gengec, Hilal
To investigate the effects of resilience and cyberbullying on students' self-esteem, predictive correlational design was employed as a method of investigation. Data were collected from 580 ninth-grade students at Anatolian High Schools. Findings of the study demonstrated that as the resilience level increases, self-esteem level increases. Also, as cyberbullying increases, self-esteem decreases.